(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effectiveness of training to enhance the training program of BSHM at Bestlink College of the Philippines. The respondents of this quantitative research are one hundred (50) students in the 4th year of the Bachelor of Science in Hospitality Management major in Hospitality Management at Bestlink College of the Philippines. The results of this study reveal that the majority of the respondents are 30 students in their 4th year, mostly 18–22 years old, and 49% are single. It reveals that leadership, meetings, incentives, conferences, exhibitions (M.I.C.E.), teamwork, and on-the-job training (OJT) are evaluated as "Very Effective" in terms of training. Financial problems, lack of confidence, and communication skills are evaluated as "Very Effective" as the most challenging for students to take their training. Based on the gathered data and conclusions drawn, this study recommends that the administration and students actively participate in all the training and activities from school that can help them reach their competency. The professor or instructor should assess students throughout the lesson and provide consistent one-on-one or small group intervention to meet the highest expectations.